IMPROVING THE BREAD QUALITY OF SUNI-BUG DAMAGED WHEAT FLOURS BY SOURDOUGH BREADMAKING AND LIQUID RYE SOUR - Ozulku, G.; Ozay, D. Sivri (AKADEMIAI KIADO ZRT, 2020)
The breadmaking quality of bug-damaged wheat flours with high protease activity (LPAWF) and low protease activity (LPAWF) was attempted to be improved by using sourdough (prepared by L. plantarum (SDI) and L. sanfrancissensis (SD2)) and liquid rye sour (LRS) in this study. The effects of sourdoughs (20 and 40%) and LRS (1 and 2%) on the protease activity of the HPAWF were determined by SDS-PAGE. Protease activity of HPAWF decreased with the addition of 40% SDI, 20% SD2, and both levels of LRS (1 and 2%) compared to a control sample. The HPAWF bread samples produced with LRS (1 and 2%) had higher volume (P 0.05), while SDI addition caused quality losses. The overall results suggested that addition of 2% LRS had promising results for improving bread quality flours that were damaged by suni-bug at low levels.
Keywords: high protease activity wheat flour; sourdough; liquid rye sour; bread quality; GLUTENIN; Food Science & Technology; Nutrition & Dietetics